2014
DOI: 10.1353/csd.2014.0062
|View full text |Cite
|
Sign up to set email alerts
|

Keeping It Frat: Exploring the Interaction Among Fraternity Membership, Disinhibition, and Hypermasculinity on Sexually Aggressive Attitudes in College-Aged Males

Abstract: This study examines correlates that contribute to sexually aggressive attitudes toward women. Using a sample that includes 217 college males from 3 southern universities, the study evaluates the relationship between college men’s hypermasculine and sexually aggressive attitudes, as well as how fraternity membership and disinhibition moderate this relationship. We hypothesized that sexually aggressive attitudes would be associated with a 3-way interaction among disinhibition, fraternity membership, and hypermas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 33 publications
1
26
0
Order By: Relevance
“…Fraternities and sororities require strict adherence to their community norms (Corprew & Mitchell, 2014;Humphrey & Kahn, 2000). If the community norms within fraternities and sororities could be changed to promote a social identity that is associated with gender equality and a willingness, perhaps even an obligation, to intervene and assist 'sisters' or 'brothers' in risky situations, there may be a significant reduction in sexual assault within the Greek community.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fraternities and sororities require strict adherence to their community norms (Corprew & Mitchell, 2014;Humphrey & Kahn, 2000). If the community norms within fraternities and sororities could be changed to promote a social identity that is associated with gender equality and a willingness, perhaps even an obligation, to intervene and assist 'sisters' or 'brothers' in risky situations, there may be a significant reduction in sexual assault within the Greek community.…”
Section: Resultsmentioning
confidence: 99%
“…Research has consistently shown that fraternity and sorority members are more likely than non-members to report traditional gender role attitudes, which promote a male-dominant, femalesubmissive model of gender (Bleecker & Murnen, 2005;Corprew & Mitchell, 2014;Kalof & Cargill, 1991;Robinson, GibsonBeverly, & Schwartz, 2004), and traditional gender role attitudes have been consistently linked to rape-supportive attitudes (Page, 2008). In a study of incoming freshmen, McMahon (2010) found that while women intending to pledge sororities were less accepting of rape myths than men intending to pledge fraternities, women intending to pledge a sorority were more accepting of rape myths than women not intending to pledge.…”
Section: Sexual Assault and Attitudes About Rape In Greek Organizationsmentioning
confidence: 99%
“…These figures illustrate an injustice to a majority of students on collegiate campuses who are seeking to gain knowledge, grow as an individual, learn to express themselves, and transition into adulthood. However, while student demographics have changed in the past half-century and the culture of many campuses redefined, little effort has been made to remake the Greek culture, which still remain primarily obedient to traditional sex roles (Corprew III and Mitchell 2014;Franklin et al 2012;Hall and Sandler 1984;Morris and Daniel 2008). When this obedience is combined with constructed ideals of identity, along with extreme partying as a recreational activity has led to an ongoing pattern of violence for at least the last half a century (Cowley 2014;Swartout et al 2015;Weiss 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Unfolding structural mechanisms for sexual assault, fraternities control social hierarchy on campus through the manipulation of the social scene (Boswell and Spade 1996;Corprew III and Mitchell 2014;Franklin et al 2012;Menning 2009;Sanday 2007;Weiss 2013). Given that fraternity houses are usually either on or close to campus, parties at these houses are usually one focal point of weekend campus activities (DeSantis 2007;Weiss 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation